Reproductive Trade-Offs in Culex pipiens: Effects of CYV Infection and Delayed Mating - Mareike Heinig-Hartberger; Fanny Hellhammer; Stefanie C. Becker (Insects)
Arbovirus control strategies often target vector reproductive dynamics, with insect-specific viruses (ISVs) like Culex Y virus (CYV) offering potential as eco-friendly approaches by influencing mosquito reproduction without affecting humans or animals. This study investigated the interplay between autogeny, anautogeny, nutrient availability, and viral infection and their effect on reproductive success in Culex pipiens biotype molestus and Culex pipiens quinquefasciatus. CYV infection had a minimal impact on mosquito reproductive parameters, even after a five-day incubation period. Autogeny enabled Cx. pipiens biotype molestus to produce eggs without blood meals, yet older females (3–5 days post-emergence) showed reduced reproductive success unrelated to nutrient deficiency, as blood-feeding did not restore their egg production. These findings demonstrate that age affects reproductive success in Cx. pipiens biotype molestus but not in Cx. pipiens quinquefasciatus and suggest that CYV has negligible direct effects on mosquito reproduction. This work enhances our understanding of ISV biology and vector ecology, supporting the development of innovative, sustainable arbovirus-control strategies.